Evaluating the effectiveness and applicability of ubiquitous-based learning about post-operative care of gastrointestinal cancer surgery for patients’ family caregivers - Vo, Thi Bich Nga; Nguyen, Thi May; Vo, Thi Diem Binh; Ho, Thi Thuy Trang; Nguyen, Thi Anh Phuong (Tạp chí Y Dược Huế, 2023)
Background: Utilizing Ubiquitous - Based Learning (UBL) in health education within the hospital setting has practical support for the patient’s care. However, the application of technology in health education programs in a hospital environment is still limited. Objectives: This study aimed to evaluate the effectiveness and applicability of UBL in the post-operative care of gastrointestinal cancer surgery for patients’ family caregivers at Department of Surgery 1, Da Nang Oncology Hospital from April 2020 to February 2022. Materials and method: A quasi-experimental study was conducted on 70 family members of patients being treated after gastrointestinal cancer surgery at Department of Surgery 1, Da Nang Oncology Hospital. Results: The effectiveness of UBL : The findings revealed no significant difference between the two groups’ knowledge scores before the intervention. However, the post-test mean scores increased in both groups; in which, the intervention group’s mean score of knowledge was significantly greater compared to the control group with 3.23 ± 0.84 and 1.82 ± 0.92 respectively (p < 0.05). The applicability of UBL: All family members agreed and completely agreed on the features of UBL in family health education about caring for patients after gastrointestinal cancer surgery. Conclusion: The teaching method utilizing UBL is significantly more effective than traditional teaching methods, and it is necessary to enhance its application in health education in hospitals and the community.